STUDI KUALITATIF TENTANG KARAKTERISTIK DAN KEBUTUHAN AKADEMIK PESERTA DIDIK SEBAGAI LANDASAN PENYUSUNAN SISTEM INSTRUKSIONAL DI MATA KULIAH PENDIDIKAN PANCASILA - Rita Mulyati; Masyadi; Samsudin; Dirgantara Wicaksono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This qualitative study aims to analyse the characteristics and academic needs of students enrolled in the Pancasila Education course. The goal is to develop a relevant and contextual instructional system based on these findings. The study employs a qualitative descriptive approach. Data were collected through semi-structured interviews with five students and open-ended questionnaires via Google Forms completed by 20 students from various faculties. The results showed that most students (65%) are visual learners, 20% are kinesthetics learners, and 15% are auditory learners. The main obstacles were the dominance of the lecture method (90%) and abstract material (85%). Students expressed a desire for case-based discussion methods (100%), learning videos (85%), and contextual approaches (90%). A significant gap exists between the instructional system designed in the RPS (with 70% lecture allocation) and student needs. These findings underscore the urgent need to develop varied, interactive, and student-cantered instructional designs for Pancasila Education courses.